Solid Lipid Nanoparticles: An Approach to Improve Oral Drug Delivery - Nestor Mendoza-Muñoz; Zaida Urbán-Morlán; Gerardo Leyva-Gómez; María de la Luz Zambrano-Zaragoza; Elizabeth ¨Piñón-Segundo; David Quintanar-Guerrero (Frontiers Media S.A., 2021)
Nanoparticles have shown overall beneficial effects in drug administration. Specifically, solid lipid nanoparticles (SLN) have emerged as an alternative to polymer-based systems. However, the oral administration of SLN, the first choice for conventional medications, has not been addressed due to the taboo surrounding the complicated transit that this delivery route entails. This review focuses on the encapsulation of drugs into SLN as a strategy for improving oral administration. Examples of applications of SLN to enhance the absorption and bioavailability of poorly-soluble drugs and protect acid-labile active molecules are discussed. This work also emphasizes the importance of developing SLN-based systems to treat health issues such as neurological diseases and cancer, and combat antibiotic resistance, three significant and increasingly common current public health problems. The review sections clarify how SLN can improve bioavailability, target therapeutic agents, and reduce side effects.